1990
DOI: 10.1105/tpc.2.12.1157
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti Genes Encoding Catabolism of Trigonelline Are Induced under Symbiotic Conditions.

Abstract: Rhizobium meliloti trc genes controlling the catabolism of trigonelline, a plant secondary metabolite often abundant in legumes, are closely linked to nif-nod genes on the symbiotic megaplasmid pSym [Boivin, C., Malpica, C., Rosenberg, C., Denarie, J., Goldman, A., Fleury, V., Maille, M., Message, B., and Tepfer, D. (1989). In Molecular Signals in the Microbe-Plant Symbiotic and Pathogenic Systems. (Berlin: Springer-Verlag), pp. 401-407]. To investigate the role of trigonelline catabolism in the Rhizobium-legu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(38 citation statements)
references
References 29 publications
(29 reference statements)
0
38
0
Order By: Relevance
“…In our previous work (Chovanec and Novák 2005) we used the reporter gene lacZ coding for ȕ-galactosidase to visualize the activity of rhizobial nodulation genes in the early symbiosis with the same host V. tetrasperma. Nevertheless, the removal of indigenous E-galactosidase background by prolonged treatment with glutaraldehyde is inevitable in this case (Boivin et al 1990). Although high sensitivity, robustness and easy detection represent the advantages of enzyme-encoding marker and reporter genes in rhizobial symbiosis (Wilson 1995), the demands for continuous monitoring of nodule development and activities favor the application of nondestructive fluorescence techniques (Xi et al 1999).…”
Section: Discussionmentioning
confidence: 96%
“…In our previous work (Chovanec and Novák 2005) we used the reporter gene lacZ coding for ȕ-galactosidase to visualize the activity of rhizobial nodulation genes in the early symbiosis with the same host V. tetrasperma. Nevertheless, the removal of indigenous E-galactosidase background by prolonged treatment with glutaraldehyde is inevitable in this case (Boivin et al 1990). Although high sensitivity, robustness and easy detection represent the advantages of enzyme-encoding marker and reporter genes in rhizobial symbiosis (Wilson 1995), the demands for continuous monitoring of nodule development and activities favor the application of nondestructive fluorescence techniques (Xi et al 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Trigonelline (10) catabolism may be more important in nodules of leguminous plants. It has been reported that trigonelline (10) is excreted from seeds of Medicago sativa, and induces nodulation (Nod) gene transcription in Rhizobium meliloti by activating the regulatory protein NodD2 (Phillips et al, 1992); R. meliloti genes encoding catabolism of trigonelline (10) are induced under symbiotic conditions (Boivin et al, 1990). Trigonelline (10) may therefore be intimately related to the symbiosis of L. japonicus and leguminous bacteria, Mesorhizobium loti and/or Bradyrhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other pyridine alkaloids, such as ricinine (Yang and Waller, 1965), nicotine and anabasin (Häkkinen et al, 2007), trigonelline (10) is a more widely distributed pyridine alkaloid, and is found in most leguminous plants (Matsui et al, 2007;Ashihara, 2008). Trigonelline (10) is produced from nicotinic acid (8) by nicotinate N-methyltransferase (EC 2.1.1.7), using S-adenosyl-L-methionine as a methyl group donor (Joshi and Handler, 1960;Upmeier et al, 1988;Chen and Wood, 2004), and is important in the symbiosis of leguminous plants and bacteria (Boivin et al, 1990;Phillips et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many micro-organisms can only utilise rather general plant metabolites, some bacteria have the capacity to catabolize certain plant secondary metabolites providing a selective advantage to colonize the rhizosphere of specific plants (Savka et al 2002). Examples of such nutritional mediators are glycosides and aryl-glycosides (Faure et al 1999(Faure et al , 2001, calystegin (Tepfer et al 1988;Guntli et al 1999), certain flavonoids (Hartig et al 1991), proline (Jiménez-Zurdo et al 1997), 1-aminocyclopropane-1-carboxylic acid (Penrose and Glick 2001), and homoserine and betaines (Boivin et al 1990;Goldmann et al 1991). Another well described effect of often unidentified components of rhizodeposits is the activation of bacterial gene expression culminating in more or less intimate interactions with the producing plant host (Stachel et al 1985;Koch et al 2002;Cooper 2007;Reddy et al 2007;Franks et al 2008;Johnston et al 2008).…”
Section: Communication In the Rhizosphere: Mechanisms And Functionsmentioning
confidence: 97%